Some heavy metals in Luciobarbus esocinus for public consumption and consumer protection - Dusukcan, M.; Canpolat, O.; Eroglu, M. (C M B Assoc, 2017)
In this study, the concentrations of some heavy metals were determined in the muscle of Luciobarbus esocinus Heckel, 1843 and in water where they live. The results were evaluated in term of potential human risk of consumption of this fish and the relationship between the heavy metal load of fish and some of their biological aspects (weight, length and sex). In addition, the accumulation factor of heavy metals in the muscle of L. esocinus were also determined. The Cr, Pb and Ni were not found in detectable levels according to results obtained by ICP. Only Cu, Zn and Fe were detected. It was found that heavy metals concentrations in the muscle of L. esocinus were higher than that in the water. The concentration of heavy metals showed differences according to weight, length and sex of fish. The results were discussed and compared with tolerable values for heavy metals provided from the EPA, FAO and WHO in order to determine whether this fish species has any risk for human consumption.
Keywords: Accumulation factor; Luciobarbus esocinus; Heavy metals; Public consumption; Consumer protection